Physiotherapy students' and clinical instructors' perceptions on effective clinical teaching and learning methods / Nur Aida Aryana Razi, Sarah Allia Ishak and Fatim Tahirah Mirza - Razi, Nur Aida Aryana; Ishak, Sarah Allia; Mirza, Fatim Tahirah (Faculty of Health Sciences, Universiti Teknologi MARA, 2022)
Introduction: Clinical education is an important component of physiotherapy education. It involves the application of hands-on practice in real working environment to produce independent physiotherapists that are committed to life-long learning and engaged in professional practice. Objectives: This study aimed to determine the perception of physiotherapy students and clinical instructors (CIs) on the effective clinical teaching and learning (T&L) methods. The difference perceptions between students and CIs were then analysed. Methods: All enrolled physiotherapy students and CIs involved in the clinical education in UiTM were invited to participate. A selfadministered questionnaire with questions adapted from previous study was distributed through an online platform. Results: 90 students and 32 CIs completed the questionnaire. Both students and CIs perceived feedback to the students (students: 1.76±0.71; CIs: 1.79±0.62) and patient-centered activities (students: 1.76±0.61; CIs: 1.91±0.58) as the most effective clinical T & L methods. The perception on effective clinical T & L methods were significantly different between students and CIs on five activities. More students feel that they learn an extreme amount on activities such as (i) student self-assessment (39% vs. 16%; p<0.05), (ii) assessment by other students (23% vs 12%; p<0.05), (iii) assessment by patients (27% vs. 9%; p<0.05), and (iv) completing clinical folder (49% vs. 25%; p<0.05). On the other hand, more CIs feel that the students learn an extreme amount participating in X-ray discussion (25% vs. 18%; p<0.05). Conclusions: Feedback from instructors and patient-centered activities were perceived to be the most effective T & L methods in the clinical setting by both students and CIs. These teaching and learning methods should be formally incorporated into clinical placement educational programs.